2019
DOI: 10.1016/j.heliyon.2019.e01622
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of starch from Limnophila aromatica

Abstract: Starch is one of the digestible natural polymers found in vascular plants. This natural polymer is the primary source of polysaccharides to produce energy for humans. In this work, starch was extracted from the defatted and dephenolated Limnophila aromatica (DFPLA) by using the alkaline method. The DFPLA contains starch with a purity of 70.43 % where 55.1 % of it is the resistant starch. Physicochemical properties of the DFPLA starch such as solubility, morphology, swelling power, crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 40 publications
(49 reference statements)
2
12
0
Order By: Relevance
“…MAE starches start the second mass loss of about 280 • C and CONV starch at 300 • C. This difference in temperature can be explained by the depolymerization of the starch generated with the extraction of microwaves, which begin to degrade faster at lower temperatures. Thermally, the starches are similar and these results were observed by other authors with starches from avocado seed and other botanical sources [9,18,[44][45][46][47].…”
Section: Thermogravimetric Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…MAE starches start the second mass loss of about 280 • C and CONV starch at 300 • C. This difference in temperature can be explained by the depolymerization of the starch generated with the extraction of microwaves, which begin to degrade faster at lower temperatures. Thermally, the starches are similar and these results were observed by other authors with starches from avocado seed and other botanical sources [9,18,[44][45][46][47].…”
Section: Thermogravimetric Analysissupporting
confidence: 88%
“…Starch is composed mainly of amylose and amylopectin that are polysaccharides composed of monomers of glucose and water. Starch has two characteristic regions of the spectrum, the -OH and -CH stretching vibration of the glucose unit, 3650-3000 cm −1 and the region of major adsorption bands or region of carbohydrate vibrations between 1200-800 cm −1 , known as fingerprint region [37,47]. The band at 2926 cm −1 corresponds to C-H stretching associated with the ring methane hydrogen atoms.…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…There was no significant difference in onset gelatinization temperature ( T o ) and gelatinization enthalpy (Δ H ) between RD43 rice flour and Hom Mali rice flour. The thermal properties are normally affected by the chemical composition, the origin of starch, moisture, the presence of other biomaterials, and processing and pretreatment conditions [ 35 ]. Previous studies have revealed a positive correlation between T p , T c , and crystallinity in rice flour [ 5 ].…”
Section: Resultsmentioning
confidence: 99%
“…The plant also has antimutagenic and antitumor properties. It contains starch, dietary fiber, protein, polysaccharides, and lignin [ 97 ].…”
Section: Some Significant Aquatic and Semiaquatic Medicinal Plantsmentioning
confidence: 99%